299 The role of mental health problems and psychotropic drug treatments in accidental injury at work. (11th October 2013) - Palmer, T; D'Angelo,; Harris, E C; Linaker, C; Coggon, D
Abstract : Objectives: some evidence exists that mental health problems and drugs with psychotropic effects may raise risks of accidental injury at work. To confirm this and to quantify risks we undertook a case-control analysis nested within the UK General Practice Research Database (GPRD). Methods: The GPRD logs all primary care information for some 6% of the British population. Medical consultations and referrals are classified by the Read system and drug prescriptions according to the British National Formulary. Using the GPRD, we identified 1, 348 patients aged 16–64 years consulting a general practitioner between 1/1/89 and 31/12/09 for a workplace injury (cases - 479 diagnostic codes) and 6, 652 age, sex, and practice-matched controls (subjects with no such consultation). Cases and controls were compared in terms of consultations for mental health problems (1, 328 diagnostic codes) and prescription of hypnotics, anxiolytics and antidepressants before the index date of injury. Associations were explored using conditional logistic regression with adjustment for recorded alcohol misuse. Results: In all, 1, 846 (23%) of the 8, 000 subjects had had at least one consultation in one/more of the coded psychiatric categories prior to the index date; 1, 682 (21%) had been prescribed one/more drugs of inquiry. Odds of injury consultation were raised 46% (P < 0.00) in those with prior mental health consultations, significant associations existing by subclass of diagnosis (psychosis, neurosis, certain other mental health conditions). Additionally, the Odds Ratio in relation to drug treatment was 1.59 (95% CI 1.38–1.83, P < 0.001) and significantly increased for each of the drug classes considered. Conclusions: Mental health problems and psychotropic treatments account for an important and potentially preventable minority of workplace injury events.